Nature and Origin of "Squirting" in Female Sexuality. (1st March 2015) - Salama, Samuel; Boitrelle, Florence; Gauquelin, Amélie; Malagrida, Lydia; Thiounn, Nicolas; Desvaux, Pierre
ABSTRACT: Introduction: During sexual stimulation, some women report the discharge of a noticeable amount of fluid from the urethra, a phenomenon also called "squirting." To date, both the nature and the origin of squirting remain controversial. In this investigation, we not only analyzed the biochemical nature of the emitted fluid, but also explored the presence of any pelvic liquid collection that could result from sexual arousal and explain a massive fluid emission. Methods: Seven women, without gynecologic abnormalities and who reported recurrent and massive fluid emission during sexual stimulation, underwent provoked sexual arousal. Pelvic ultrasound scans were performed after voluntary urination (US1), and during sexual stimulation just before (US2) and after (US3) squirting. Urea, creatinine, uric acid, and prostatic‐specific antigen (PSA) concentrations were assessed in urinary samples before sexual stimulation (BSU) and after squirting (ASU), and squirting sample itself (S). Results: In all participants, US1 confirmed thorough bladder emptiness. After a variable time of sexual excitation, US2 (just before squirting) showed noticeable bladder filling, and US3 (just after squirting) demonstrated that the bladder had been emptied again. Biochemical analysis of BSU, S, and ASU showed comparable urea, creatinine, and uric acid concentrations in all participants. Yet, whereas PSA was not detected in BSU in six out of seven participants, this antigen was present in S and ASU in five out of seven participants. Conclusions: The present data based on ultrasonographic bladder monitoring and biochemical analyses indicate that squirting is essentially the involuntary emission of urine during sexual activity, although a marginal contribution of prostatic secretions to the emitted fluid often exists.